IbM PENGEMBANGAN PRODUKSI TELUR ASIN â€œSIFAHâ€, DESA GESING, BANJAR SARI, BUDURAN, SIDOARJO, JAWA TIMUR - Benny Bintarjo; Farida Murti; Mufidah .; Achmad Wahana Karimullah; Moh. Hazazi Kirom (JPM17: Jurnal Pengabdian Masyarakat, 2016)
Salted Egg needs for to be consumed or for event in Sidoarjo is growing upfaster. Unfortunetely, the producer of salted egg couldnâ€™t serve at all. In thiscase by â€œSifahâ€ a salted eggs producer partner. The obstacled is longerproduction time to produce an egg. Based for result of the survey, the mostlonger time out is on washing process between 8 hours per day with 3 â€“ 5servant. Depend on our partner deals, the inefficiently could be solve by an ideaof washing egg machine. This machine is a solution of cleaning process from dirtthings on the egg. Beside that, it can reduced amount of labour. Manual work ofthe machine can cleaning 12 eggs in the one time and need just 2 minutes for tocomplete it with load power of dynamo is 125 watt. Cleaning process will makesthe egg wet and brushes the egg in time and speed managed condition by oneoperator controller. Result of appropriate technology can cleaning 1400 eggs on4 hours by one operator controller. With the result, it can complete the everyconsumer orders.Keywords : machine, washes, egg, efficient